E-BANKING APPLICATION INFORMATION SYSTEM IN SHARIA BANK: Sharia Banking, Information System, E-Banking - Novi Sofwatunnisa; Muizz Doni Kurniawan; Muhammad Ilhan Manzis; Hardian Rifanza; Suryo Budi Santoso (JPIM (Jurnal Penelitian Ilmu Manajemen), 2023)
The purpose of this study is to determine the management information system used to implement the use of E-banking at Islamic banks using digital technology in the form of gadgets or smartphones. Islamic economic growth has entered Indonesia's broad economic policy framework, so that sharia-based banking has become the driving force for the development of traditional banks. In carrying out its activities, Islamic banks utilize information technology to form and create systems in Islamic banking, namely a special application that can facilitate transaction procedures for customers so that Islamic banks can be said to be relatively good at applying technology.